Redundant roles of four ZIP family members in zinc homeostasis and seed development in Arabidopsis thaliana. (8th October 2021) - Lee, Sichul; Lee, Joohyun; Ricachenevsky, Felipe K.; Punshon, Tracy; Tappero, Ryan; Salt, David E.; Guerinot, Mary Lou
SUMMARY: Zinc (Zn) is essential for normal plant growth and development. The Zn‐regulated transporter, iron‐regulated transporter (IRT)‐like protein (ZIP) family members are involved in Zn transport and cellular Zn homeostasis throughout the domains of life. In this study, we have characterized four ZIP transporters from Arabidopsis thaliana (IRT3, ZIP4, ZIP6, and ZIP9) to better understand their functional roles. The four ZIP proteins can restore the growth defect of a yeast Zn uptake mutant and are upregulated under Zn deficiency. Single and double mutants show no phenotypes under Zn‐sufficient or Zn‐limited growth conditions. In contrast, triple and quadruple mutants show impaired growth irrespective of external Zn supply due to reduced Zn translocation from root to shoot. All four ZIP genes are highly expressed during seed development, and siliques from all single and higher‐order mutants exhibited an increased number of abnormal seeds and decreased Zn levels in mature seeds relative to wild type. The seed phenotypes could be reversed by supplementing the soil with Zn. Our data demonstrate that IRT3, ZIP4, ZIP6, and ZIP9 function redundantly in maintaining Zn homeostasis and seed development in A . thaliana . Significance Statement: Deficiencies of micronutrients commonly limit plant growth and crop yields. Furthermore, as most people rely on plants as their dietary source of micronutrients, plants that serve as better sources of essential nutrients would improve human health. The use of higher‐order mutants has allowed us to show that four of the A. thaliana ZIP transporters, IRT3, ZIP4, ZIP6, and ZIP9, function redundantly in maintaining Zn homeostasis and in seed development.